Buscando el (buen) sentido en la transformación del sistema alimentario en México a través de las narrativas contrahegemónicas emergentes en las comunidades indígenas y rurales de Oaxaca - Denham, Diana (2024)
Mexico is in the grips of a public health crisis related to its changing food system, characterized by dramatic increases in diet-related illness. Ideas about how to reverse these trends stretch from top-down nutrition education to demands for regulation of the food and beverage industry. Taking a different approach, this paper focuses on the perspectives and practices of rural Oaxacans, drawn from qualitative research conducted in seven communities over six years. We find an emergent critique of the contemporary capitalist food system rooted in embodied engagements with food production, preparation, consumption, and community history. We analyze these findings through the lens of Gramsci’s concept of ‘good sense,’ understood as the critical-thinking basis for revolutionary transformation among subaltern classes. We situate this idea within literature on embodied knowledge and visceral politics, suggesting that such ideas and perceptions have the potential to challenge the growing hegemony of the corporate food system and contribute to broader social movements in defense of land and life.